2012
DOI: 10.1021/nn303548z
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Intercalation under Graphene on Ir(111): Energetics, Kinetics, and the Role of Graphene Edges

Abstract: Using X-ray photoemission spectroscopy (XPS) and scanning tunneling microscopy (STM) we resolve the temperature-, time-, and flake size-dependent intercalation phases of oxygen underneath graphene on Ir(111) formed upon exposure to molecular oxygen. Through the applied pressure of molecular oxygen the atomic oxygen created on the bare Ir terraces is driven underneath graphene flakes. The importance of substrate steps and of the unbinding of graphene flake edges from the substrate for the intercalation is ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
183
3
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(215 citation statements)
references
References 34 publications
25
183
3
4
Order By: Relevance
“…In these hybrid devices the N areas can be obtained by decoupling locally the graphene from the substrate in a controlled way. Among other methods, this could be achieved by intercalation [34][35][36].…”
Section: Fig 3 (Color On Line) Top: Topographic Image (5×3 Nmmentioning
confidence: 99%
“…In these hybrid devices the N areas can be obtained by decoupling locally the graphene from the substrate in a controlled way. Among other methods, this could be achieved by intercalation [34][35][36].…”
Section: Fig 3 (Color On Line) Top: Topographic Image (5×3 Nmmentioning
confidence: 99%
“…It consists of the preparation of graphene on metallic or semiconducting layers via standard chemical vapour deposition (CVD) technique or intercalation under graphene, followed by the oxidation of the underlying metal or semiconductor at relatively high pressure of oxygen. This procedure was used in several recent works, where nearly free-standing graphene on bulk or surface oxide layers was prepared [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Surface science studies on the well-defined graphene/metal surfaces have shown that gaseous molecules such as CO, O 2 , and H 2 O can be readily intercalated under the graphene overlayers (21-27). Defects in graphene including island edges (22,23,(28)(29)(30), domain boundaries (26,31,32), and wrinkles (33) provide channels for molecule diffusion into the graphene/metal interfaces. These new results raise the intriguing possibility that the space between graphene overlayers and metal substrates can act as a 2D container for reactions.…”
mentioning
confidence: 99%